CHARACTERISATION OF ACTIVATED CARBON FROM WHITE SNAPPER SCALES (Lates calcarife) WASTE - Jolantje Latupeirissa; Matheis F. J. D. P. Tanasale; Eirene G. Fransina; Semuel Simra Pada; Muliana Muliana (JURNAL KIMIA MULAWARMAN, 2024)
ABSTRACT Research on the characterisation of activated carbon of white snapper (Lates calcarifer) scales waste, obtained through carbonisation process, fish scales were put in a furnace at 350 oC for 2 hours. Then cooled and sieved with a 100 mesh sieve, characterised by XRD, resulting in three peaks with the strongest intensity at 2θ regions of 26.45o, 32.69o, and 33.60o respectively. The surface acidity of carbon solids before and after activation were (4.48x10-3 and 7.77x10-3) mol/g, respectively. The activation process of white snapper scales (Lates calcarifer), increases the surface area of carbon can react with other chemicals. Subsequently, it was calcined at 450 oC under vacuum conditions for 2 hours with N2 gas, and characterised by XRD. The results showed a shift in 2θ peaks of 26.52o, 29.66o, and 32.77o, respectively. The carbon was activated by soaking with 3 M KOH activator for 15 hours, washed with distilled water, and dried in an oven at 110°C for 1 hour, characterised by XRD, and the peaks with the strongest intensity were obtained at 26.22°C, 29.12°C, and 32.43°C, with increasing basal spacing. Keywords: activated carbon, white snapper scales, XRD